Mitochondria Matter: Systemic Aspects of Nonalcoholic Fatty Liver Disease (NAFLD) and Diagnostic Assessment of Liver Function by Stable Isotope Dynamic Breath Tests - Di Ciaula, Agostino (Int J Mol Sci, 2021)
The liver plays a key role in systemic metabolic processes, which include detoxification, synthesis, storage, and export of carbohydrates, lipids, and proteins. The raising trends of obesity and metabolic disorders worldwide is often associated with the nonalcoholic fatty liver disease (NAFLD), which has become the most frequent type of chronic liver disorder with risk of progression to cirrhosis and hepatocellular carcinoma. Liver mitochondria play a key role in degrading the pathways of carbohydrates, proteins, lipids, and xenobiotics, and to provide energy for the body cells. The morphological and functional integrity of mitochondria guarantee the proper functioning of β-oxidation of free fatty acids and of the tricarboxylic acid cycle. Evaluation of the liver in clinical medicine needs to be accurate in NAFLD patients and includes history, physical exam, imaging, and laboratory assays. Evaluation of mitochondrial function in chronic liver disease and NAFLD is now possible by novel diagnostic tools. “Dynamic” liver function tests include the breath test (BT) based on the use of substrates marked with the non-radioactive, naturally occurring stable isotope (13)C. Hepatocellular metabolization of the substrate will generate (13)CO(2), which is excreted in breath and measured by mass spectrometry or infrared spectroscopy. Breath levels of (13)CO(2) are biomarkers of specific metabolic processes occurring in the hepatocyte cytosol, microsomes, and mitochondria. (13)C-BTs explore distinct chronic liver diseases including simple liver steatosis, non-alcoholic steatohepatitis, liver fibrosis, cirrhosis, hepatocellular carcinoma, drug, and alcohol effects. In NAFLD, (13)C-BT use substrates such as α-ketoisocaproic acid, methionine, and octanoic acid to assess mitochondrial oxidation capacity which can be impaired at an early stage of disease. (13)C-BTs represent an indirect, cost-effective, and easy method to evaluate dynamic liver function. Further applications are expected in clinical medicine. In this review, we discuss the involvement of liver mitochondria in the progression of NAFLD, together with the role of (13)C-BT in assessing mitochondrial function and its potential use in the prevention and management of NAFLD.